The Role of Performance Quality in Adolescents' Self-Evaluation and Rumination after a Speech: Is it Contingent on Social Anxiety Level?. Issue 2 (17th May 2018) - Blöte, Anke W.; Miers, Anne C.; Van den Bos, Esther; Westenberg, P. Michiel
Abstract : Background: Cognitive behavioural therapy (CBT) has relatively poor outcomes for youth with social anxiety, possibly because broad-based CBT is not tailored to their specific needs. Treatment of social anxiety in youth may need to pay more attention to negative social cognitions that are considered a key factor in social anxiety development and maintenance.Aims: The aim of the present study was to learn more about the role of performance quality in adolescents' cognitions about their social performance and, in particular, the moderating role social anxiety plays in the relationship between performance quality and self-cognitions.Method: A community sample of 229 participants, aged 11 to 18 years, gave a speech and filled in questionnaires addressing social anxiety, depression, expected and self-evaluated performance, and post-event rumination. Independent observers rated the quality of the speech. The data were analysed using moderated mediation analysis.Results: Performance quality mediated the link between expected and self-evaluated performance in adolescents with low and medium levels of social anxiety. For adolescents with high levels of social anxiety, only a direct link between expected and self-evaluated performance was found. Their self-evaluation was not related to the quality of their performance. Performance quality also mediated the link between expected performance and rumination, but social anxiety did not moderate this mediation effect.Conclusions: Results suggest that a good performance does not help socially anxious adolescents to replace their negative self-evaluations with more realistic ones. Specific cognitive intervention strategies should be tailored to the needs of socially anxious adolescents who perform well.